The Role of Consumer Confidence in Effect of Islamic Business Ethics on Religius Tourism Marketing - Sunaidah, Siti; M. Maghfiroh, Ana M. Maghfiroh; Muniri, Muniri; Sakti Delviero, Alexandro Sakti Delviero (Management Department, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Ampel Surabaya, 2026)
The Sharia tourism industry has witnessed remarkable growth in recent years, becoming one of the most dynamic sectors within the global travel market. According to recent data, the number of Muslim tourists reached approximately 230 million in 2023, demonstrating the increasing demand for tourism products and services that comply with Sharia principles. This growing market highlights the potential of Islamic-based tourism not only as a spiritual journey but also as a driver of economic and cultural development. Despite this progress, one of the most persistent challenges in the development of Sharia tourism is ensuring the consistent application of Islamic values in all aspects of service delivery and business operations. Many destinations still struggle to maintain a balance between commercial objectives and adherence to Sharia norms, particularly in providing facilities that align with Muslim travelers’ expectations of halal, ethical, and value-based experiences. This study seeks to examine the role of consumer confidence in mediating the relationship between Islamic business ethics and religious tourism marketing effectiveness at the Ar-Rahman Mosque Tourism Site in Blitar District. The research employed a quantitative approach using survey data collected from 150 respondents through purposive sampling. The structured questionnaire utilized a 5-point Likert scale to measure key variables related to ethical perception, consumer trust, and marketing performance. Data analysis was performed using multiple linear regression with SPSS version 26.0. The findings reveal that Islamic business ethics—particularly the principles of honesty (ash-shidq), justice (al-‘adl), responsibility (al-mas’uliyyah), and transparency—have a positive and significant effect on the marketing of Sharia-based tourism. Furthermore, consumer confidence acts as a crucial intermediary that strengthens the impact of ethical practices on marketing effectiveness. This suggests that when religious tourism providers consistently uphold Islamic ethical standards, they not only foster trust among Muslim tourists but also enhance the overall competitiveness and sustainability of the Sharia tourism sector.